Restriction on the Rights of Secured Creditors in Bankruptcy Proceedings - Yulianto (Fakultas Hukum Universitas Hang Tuah, 2017)
The enactment of Law No. 37/2004 upon Bankruptcy and Suspension of Payment (UUK-PKPU) as the “lex specialist” of the Collateral Law and Civil law has caused several legal problems to the creditors holding collateral over assets of their debitors, commonly known as secured creditors, in terms of management and settlement on bankruptcy estate. Such problems included: First, there is a normative conflict between Bankruptcy law and collateral law, in particular regarding to the principle of executorial and the principle of preference right. Second, there is a restriction on the right of secured creditors in terms of management and settlement on bankruptcy estate.